2020
DOI: 10.1038/s41598-020-65578-w
|View full text |Cite
|
Sign up to set email alerts
|

Social environment modulates investment in sex trait versus lifespan: red deer produce bigger antlers when facing more rivalry

Abstract: theory predicts that the plastic expression of sex-traits should be modulated not only by their production costs but also by the benefits derived from the presence of rivals and mates, yet there is a paucity of evidence for an adaptive response of sex-trait expression to social environment. We studied antler size, a costly and plastic sex trait, and tooth wear, a trait related to food intake and longevity, in over 4,000 male Iberian red deer (Cervus elaphus hispanicus) from 56 wild populations characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 93 publications
1
29
2
Order By: Relevance
“…This points out that pelt biting can be useful to identify individuals that are being bullied and apply corrective measures consequently (e.g., move the bullied animal to a new group structure; identify and remove the bully animal from the group). In deer hunting ranches, where density reaches up to 0.4 deer/ha and food supplementation takes place when graze is scarce, pelt biting is infrequent, based on observations over four thousand legally culled red deer to which we had access to take samples for research purposes over several years [ 26 , 47 ], and we never found a case in which pelt biting exceeded class 1.7. This is expected, as free-ranging conditions hardly create favourable conditions for bullying; population density is generally low, sufficient space precludes oversized groups, and graze is widely dispersed and therefore difficult to defend and of low energy reward value per food item [ 48 ], although there are exceptions [ 4 , 22 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This points out that pelt biting can be useful to identify individuals that are being bullied and apply corrective measures consequently (e.g., move the bullied animal to a new group structure; identify and remove the bully animal from the group). In deer hunting ranches, where density reaches up to 0.4 deer/ha and food supplementation takes place when graze is scarce, pelt biting is infrequent, based on observations over four thousand legally culled red deer to which we had access to take samples for research purposes over several years [ 26 , 47 ], and we never found a case in which pelt biting exceeded class 1.7. This is expected, as free-ranging conditions hardly create favourable conditions for bullying; population density is generally low, sufficient space precludes oversized groups, and graze is widely dispersed and therefore difficult to defend and of low energy reward value per food item [ 48 ], although there are exceptions [ 4 , 22 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two groups of hypotheses were tested on the response of pelt biting, related to (i) the hierarchical rank of the deer and related body traits, which correlate positively with successful outcome in competition for resources, and (ii) the abiotic environmental stress where they live ( Table 1 ). It is hypothesised that males individuals (H4) [ 26 ], younger individuals (H3), lower hierarchical rank individuals (H1), smaller body size (i.e., body weight, H2) individuals, and those exposed to heat stress (H6) suffer higher rates of pelt biting ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Both antler and body size are continuous traits, and the dark ventral patch may act as an amplifier for them [ 49 ] reducing the error in communication. Also, such a discrete nature of the ventral patch size suggests that trait expression not only provides information on male quality [ 27 ], but it may also reveal a behavioural strategy, like it has been shown for discrete signals in other species [ 66 68 ], of rival challenging, or willingness to be involved in competition for mates.…”
Section: Discussionmentioning
confidence: 99%
“…them [49] reducing the error in communication. Also, such a discrete nature of the ventral patch size suggests that trait expression not only provides information on male quality [27], but it may also reveal a behavioural strategy, like it has been shown for discrete signals in other species [66][67][68], of rival challenging, or willingness to be involved in competition for mates. Contrary to other morphological traits, the dark ventral patch can be modulated in the short term by urine spraying [28], which suggests a fine tune in communication during the mating season compared to body or antler size.…”
Section: Plos Onementioning
confidence: 95%
See 1 more Smart Citation